Life Satisfaction and Perceived Social Support and the Relationship Between them among a Sample of Breast Cancer Patients - Tashtoush, Rami (Jordan Journal of Educational Sciences, 2015)
This study aimed to reveal the life satisfaction and perceived social support level and the relationship between them among breast cancer patients. The sample of the study consisted of (215) breast cancer patients. The results of the study showed that breast cancer patients have medium level of life satisfaction, and there are statistically significant differences in the life satisfaction due to the variables of age, marital status, educational level, the stage of treatment, and the duration of the disease. Also, the results of the study showed that breast cancer patients have high level of perceived social support, and there are statistically significant differences in the perceived social support due to the variable of the duration of the disease. There were no statistically significant differences in the perceived social support due to the variables of age, marital status, educational level, and the stage of treatment. Finally, the study showed statistically positive relationship between life satisfaction and perceived social support